EVALUASI KINERJA ALAT CALCINER DITINJAU DARI EFESIENSI THERMAL DAN EMISI GAS CO2 DI PABRIK II PT SEMEN BATURAJA Tbk - Wijaya, Rama; Purnamasari, Indah; Kristiyono Putro, Abraham Abimanyu; Safaruddin, Safaruddin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The role of thermal efficiency of the calciner is very important because it describes the performance of the calciner, whether or not the performance of the calciner can be seen from the efficiency of the thermal calciner. The thermal efficiency of the calciner obtained based on the calculation of the Mass Balance and Heat Balance ranges from 75,59%-79,74% with an average actual thermal efficiency of 77,26% while for the average heat loss of 22,74%. The results of efficiency calculations show that the performance of the calciner tool in terms of thermal efficiency of the calciner unit is quite efficient and still good for use, because it is characterized by the efficiency of the thermal calciner unit is still included in the range of thermal calciner efficiency by design. From the average amount of CO2 produced from calcination of 100.033,7376 kg/hour and fuel combustion of 43.201,24151 kg/hour, will have an adverse impact on the quality of the surrounding air. So it must be minimized in the use of coal and maximize efficiency in the kiln system.